2022
DOI: 10.12669/pjms.38.4.4681
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of neuropathic pain and its effects on rehabilitation outcomes, balance function and quality of life among people with traumatic spinal cord injury

Abstract: Background & Objectives: Traumatic Spinal cord injury (SCI) is a devastating condition that results in life long disability. Impairments associated with traumatic SCI such as sensory, motor, and autonomic dysfunctions lead to an array of secondary SCI-specific complications. Neuropathic pain is one of the most common medical complications of traumatic SCI which significantly affects motor function and activities of daily living (ADL) in people with traumatic SCI. Neuropathic pain is one of the main factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our study’s findings that burn patients with NP report worse physical and psychosocial outcomes correlate with those experiencing NP after other traumatic injuries. In patients recovering from traumatic spinal cord injury, NP is associated with worse quality of life, a more tenuous rehabilitation course, and increased risk for worse psychological sequelae 24,25 . Our BMS study found after controlling for covariates, risk factors associated with NP after burn injury included patient characteristics such as sex, reported pain levels, ethnicity, and employment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our study’s findings that burn patients with NP report worse physical and psychosocial outcomes correlate with those experiencing NP after other traumatic injuries. In patients recovering from traumatic spinal cord injury, NP is associated with worse quality of life, a more tenuous rehabilitation course, and increased risk for worse psychological sequelae 24,25 . Our BMS study found after controlling for covariates, risk factors associated with NP after burn injury included patient characteristics such as sex, reported pain levels, ethnicity, and employment.…”
Section: Discussionmentioning
confidence: 66%
“…In patients recovering from traumatic spinal cord injury, NP is associated with worse quality of life, a more tenuous rehabilitation course, and increased risk for worse psychological sequelae. 24,25 Our BMS study found after controlling for covariates, risk factors associated with NP after burn injury included patient characteristics such as sex, reported pain levels, ethnicity, and employment. These findings are consistent with the current literature, which also identifies substance/tobacco use to be risk factors for NP development.…”
Section: Discussionmentioning
confidence: 88%